PENGHIDUPAN KEMBALI TAMAN PANATAYUDA SEBAGAI TITIK AWAL MEMBANGKITKAN KECAMATAN KARAWANG BARAT DI KABUPATEN KARAWANG - Novia Christian Wijaya; Mieke Choandi (Jurusan Arsitektur dan Perencanaan, 2022)
West Karawang Regency was originally referred to as the “Barn of Rice” because it produces rice in large quantities even to foreign countries. However, in 1980 Karawang changed its function into an industrial area which resulted in lowering the green area in Karawang. As a result, there is degradation between sub-districts in Karawang Regency. Including in West Karawang District, especially the city park, namely Panatayuda Park, which is increasingly quiet due to the lack of urban development. In fact, this sub-district is passed directly by the Pantura Road which incidentally is always passed by vehicles and people from various regions. Panatayuda Park is getting more and more shabby and not well maintained which results in a bad image of the Regency and a decline in the welfare of the local community. The method applied in the design uses case study observations, field conservation and interviews, in order to understand and apply urban acupuncture, architecture and everyday life in design. The results of this program are functions in Panatayuda Park in the form of sports areas, culinary centers, and green open spaces. Keywords: Architecture and Daily Life; City Image; Degradation; Karawang Regency; Urban Acupuncture Abstrak Kabupaten Karawang Barat pada mulanya disebut sebagai “Lumbung Padi” karena menghasilkan beras dalam jumlah yang besar bahkan sampai ke mancanegara. Namun, pada tahun 1980 Karawang beralih fungsi menjadi kawasan industri yang mengakibatkan menurunkan area hijau di Karawang. Akibatnya, terjadi degradasi antar kecamatan di Kabupaten Karawang. Termasuk pada Kecamatan Karawang Barat terutama taman kota yakni Taman Panatayuda yang kian tahun semakin sepi akibat kalahnya perkembangan kota. Padahal kecamatan ini dilewati secara langsung oleh Jalan Pantura yang notabenenya selalu dilewati kendaraan maupun orang dari berbagai daerah. Taman Panatayuda pun semakin kumuh dan tidak terawat yang berakibat pada buruknya gambaran Kabupaten dan menurunnya kesejahteraan masyarakat setempat. Metode yang diterapkan dalam rancangan menggunakan pengamatan studi kasus, konservasi lapangan dan wawancara, agar paham dan menerapkan urban akupuntur, arsitektur dan keseharian dalam desain. Hasil program ini adalah fungsi-fungsi di Taman Panatayuda yang berupa area olahraga, pusat kuliner, dan ruang terbuka hijau.